Karakteristik Morfologi dan Kelimpahan Populasi Parasitoid (Hymenoptera) pada Hama Invasif Kutu Putih Ubi Kayu, Phenacoccus manihoti Matile-Fererro (Hemiptera: Pseudococcidae) di Bali - YUDHA, I KADEK WISMA; SUPARTHA, I WAYAN; SUSILA, I WAYAN (Agrotrop : Journal on Agriculture Science; Vol 10 No 2 (2020), 2020)
Morphological Characteristics and Populations Abundance of Parasitoid (Hymenoptera) on Invasive Pests Cassava Mealybug, Phenacoccus manihoti Matile-Fererro (Hemiptera: Pseudococcidae) in Bali . This study aims to know the morphological characteristics of parasitoid, population abundance and distribution patterns of parasitoid associated with P. manihoti on cassava crop in Bali. The study was conducted on all cassava crop in Bali with a field observation method that was determined by taking shoots of cassava plants attacked by cassava mealybug P. manihoti , then cassava mealybug P. manihoti were nurtured, then observation was carried out every day until parasitoid appeared and being identified. The results of the study showed that there were three dominant types of parsitoid that were found to be associated with invasive pest P. manihoti , namely Anagyrus lopezi , Acerophagus papayae and Blepyrus insularis . The abundance of parasitoid populations was dominated by parasitoid A. lopezi with a range of values 48.6–81.8%. Then followed by parasitoid A. papayae 7.7 - 37.1%, and B. insularis 3.4 - 14.3%. The distribution pattern of parasitoid varies in each species, parasitoid A. lopezi spreads in groups categories, Parasitoid A. papayae and B. insularis spread random-regulary on cassava crop throughout on each of the Regencies in Bali.